DEVELOPMENT SOCIAL ARITHMETIC MODULE USING PROBLEM SOLVING APPROACH ON SMP / MTS CLASS VII - Wahyu Melani; Aris Thobirin (Universitas Ahmad Dahlan, 2017)
Teaching materials to help students understand the concept of social arithmetic and attract the attention of students is still lacking and does not motivate students in the learning process becomes a problem to do the research. Math module is one alternative teaching materials that can be used in the learning process. This research aims to develop a social arithmetic module using a problem solving approach students of class VII and assess the feasibility of the product being developed. The development of research in the Research and Development (R & D). Subjects were expert assessment of the product, math teacher of MTs Class VII and students of class VII MTs. Subjects to be tested in this study were students of class VII of MTs Maguwoharjo Sleman. The research instrument used was a questionnaire and the type of data used is the quantitative and qualitative data. Data collection techniques used were interview, documentation and questionnaires. Data analysis techniques were used: (1) data analysis product assessment by subject matter experts and media experts, (2) data analysis product trials, analysis of trial data usage. The results of the research and development of social arithmetic module using a problem solving approach to the VII class of SMP / MTs. The results of the feasibility test of the material included in both criteria with an average score of 29.5 out of a maximum score of 40. For the feasibility study media included in both criteria with an average score of 30 out of a maximum score of 40. While the results of the student questionnaire responses into the product trials both criteria with an average score of 39 out of a maximum score of 48. The results of the questionnaire responses of students to test usage included in both criteria with an average score of 39.22 out of a maximum score of 48. The results shown that social arithmetic material module using a problem solving approach to the claass VII in SMP / MTs eligible for use in the learning process.